Faster and farther towards the abyss: global health accelerators instead of tangible changes - Jens Holst (BMC, 2024)
Abstract Global health accelerators have become the leading expression of global health engagement and policy. While accelerators seem to be the strategy of the moment, the term is meaningless and devoid of any statement of content. Moreover, acceleration can make social processes too fast to be subject to rational control or governance, especially in an era of (un-)social media, which makes the pace of communication and information. Under the dominance of neoliberalism, acceleration and accelerators pose a particular risk because they encounter a situation in which mankind is moving away from solving vital challenges and addressing their root causes. The fashionable emergence of accelerators cannot inspire confidence in the future trends in global health unless they actually result in tangible change and new approaches to tackling systemic challenges.